Design strategies for composite matrix and multifunctional polymeric scaffolds with enhanced bioactivity for bone tissue engineering - Kumari, Shikha; Katiyar, Soumya; Darshna,; Anand, Aditya; Singh, Divakar; Singh, Bhisham Narayan; Mallick, Sarada Prasanna; Mishra, Abha; Srivastava, Pradeep (Frontiers in Chemistry, 2022)
Over the past few decades, various bioactive material-based scaffolds were investigated and researchers across the globe are actively involved in establishing a potential state-of-the-art for bone tissue engineering applications, wherein several disciplines like clinical medicine, materials science, and biotechnology are involved. The present review article’s main aim is to focus on repairing and restoring bone tissue defects by enhancing the bioactivity of fabricated bone tissue scaffolds and providing a suitable microenvironment for the bone cells to fasten the healing process. It deals with the various surface modification strategies and smart composite materials development that are involved in the treatment of bone tissue defects. Orthopaedic researchers and clinicians constantly focus on developing strategies that can naturally imitate not only the bone tissue architecture but also its functional properties to modulate cellular behaviour to facilitate bridging, callus formation and osteogenesis at critical bone defects. This review summarizes the currently available polymeric composite matrices and the methods to improve their bioactivity for bone tissue regeneration effectively.